Insights From Verbal Protocols Of Esl Writers’ Response To Written Feedback - Sharmini, Sharon (2010)

(untitled)
Feedback is essential for the development of ESL writing skills. The responses that lecturers provide on students‟ writing are essential to encourage and develop students‟ writing. However, there is a paucity in the literature as to how students attend to feedback. This study investigated the thought processes of six ESL postgraduate students as they attended to written feedback. Using a case study qualitative approach, concurrent verbal protocols of the writers were recorded as they attended to written feedback. Written texts and lecturer comments supplemented the data. The findings indicate that written feedback encouraged the writers to plan, justify, reflect and evaluate recursively. A second finding is that statement, question and imperative types of feedback encouraged recursiveness.This study concludes by suggesting that it is important for lectures to be aware of the impact of feedback. The study also suggests that the think aloud method is useful as a tool in teaching ESL writing to help student writers to reflect on the feedback and develop their writing.